MUSIC THERAPY (AN INNOVATION): संगीत चिकित्सा (एक नवाचार) - Soni, Amrita (International Journal of Research -GRANTHAALAYAH, 2015)
Narad ji once asked Lord Shri Vishnu where do you live. Then he said, O Narada, neither do I live in Baikunth nor in the heart of yogis. But I am present in a tangible form where my devotees sing. (Narada Bhakti Sutra) New experiments are taking place in the human world full of knowledge and science. When these experiments become an integral part of life, then the human being then moves into innovative research. Although music itself is a science, yet years of austerity are required for its achievement. Here, for some time, the attention of scientists has gone towards music, but due to lack of functional knowledge of music, not every scientist can pay attention to it. भगवान श्री विष्णु से एक बार नारद जी ने पूछा आप कहां रहते हैं। तब उन्होंने कहा हे नारद ना ही मैं बैकुण्ठ में रहता हूं और ना ही योगियों के हृदय मे।ं लेकिन मेरे भक्त जहां गायन वादन करते हैं वहां मैं मूर्त रूप में उपस्थित रहता हूं। (नारद भक्ति सूत्र) ज्ञान-विज्ञान से परिपूर्ण मानव-जगत में नित नए प्रयोग हो रहे हैं। जब ये प्रयोग जीवन के अभिन्न अंग बन जाते हैं, तब मानव फिर अभिनव अनुसंधान में प्रवृत्त हो जाता है। यद्यपि संगीत स्वयं एक विज्ञान है, किन्तु अभी उसकी सिद्धी के लिए वर्षों की तपस्या अपेक्षित है। इधर कुछ समय से वैज्ञानिकों का ध्यान संगीत की ओर गया है, लेकिन संगीत के क्रियात्मक ज्ञान के अभाव के कारण हर वैज्ञानिक इस ओर ध्यान नहीं दे सकता।